2015
DOI: 10.4049/jimmunol.1402160
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-3 Acts as a Modulator of B Cell Fate and Function

Abstract: The mechanisms responsible for the generation of a mature B1 and B2 cell compartment are still poorly understood. In this study, we demonstrated that absence of Dickkopf-3 (DKK3) led to changes in the composition of the B cell compartment, which were due to an altered development and maintenance program of B cells. Development of B2 cells was impaired at the pre- and immature B cell stage, resulting in decreased numbers of follicular B cells in adult DKK3-deficient mice. Furthermore, DKK3 limited B1 cell self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Although DKK3 is a relatively less-studied protein particularly in obstetrics, the highest DKK3 levels are found in organs classically considered as immune privileged, such as the embryo, placenta, and uterus [15, 36]. Importantly, recent reports demonstrated that DKK3 functions as a tissue-derived modulator of T-cell responses as well as a modulator of B-cell fate and maintenance [37, 38], suggesting that DKK3 may play an important role in the final common pathway of term and preterm parturition [39]. Therefore, DKK3 can be a potentially valuable target for diagnostic, prognostic, and therapeutic approaches to threatened preterm birth related to infectious and noninfectious etiologies; thus, this will be confirmed in the CVF, AF, and serum samples by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although DKK3 is a relatively less-studied protein particularly in obstetrics, the highest DKK3 levels are found in organs classically considered as immune privileged, such as the embryo, placenta, and uterus [15, 36]. Importantly, recent reports demonstrated that DKK3 functions as a tissue-derived modulator of T-cell responses as well as a modulator of B-cell fate and maintenance [37, 38], suggesting that DKK3 may play an important role in the final common pathway of term and preterm parturition [39]. Therefore, DKK3 can be a potentially valuable target for diagnostic, prognostic, and therapeutic approaches to threatened preterm birth related to infectious and noninfectious etiologies; thus, this will be confirmed in the CVF, AF, and serum samples by further studies.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that DKK3 contributed to the immuno-suppressive microenvironment protecting transplanted, class-I mismatched embryoid bodies from T-cell-mediated rejection ( 21 ). DKK3 is also involved in regulating the composition of the B cell compartment ( 23 ). The development of B2 cells was impaired at the pre- and immature B cell stage in the absence of DKK3, resulting in decreased numbers of follicular B cells in adult DKK3-deficient mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, DKK3 limited B1 cell self-maintenance in the periphery, by decreasing the survival and proliferation of B1 cells. In addition, DKK3-deficient mice exhibited altered antibody responses and an increased secretion of the cytokine IL-10 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…RYBP appears to be a key actor maintaining B-2 progenitors as the dominant adult B lymphocyte precursors, and it also inhibits B-1P expansion. A number of genes in mouse mutant or transgenic lines have been associated with increased numbers of mature B-1 cells (39,(45)(46)(47)(48), but to our knowledge, only Rybp has been involved in targeting adult B-1P expansion.…”
Section: Discussionmentioning
confidence: 99%